Learning Strategies of a Part Time Job Student With Good Achievement: A Case Study of a Successful Part Time Job EFL Learner - Rigel Sampelolo (LPPM UKI Toraja, 2017)
This research intended to find out the comprehensive description about learning strategies applied by the part time job University student at Christian University of Indonesia Toraja, The method used in this research was grounded theory. The instruments were interview, direct observation, and documentation. The participant of the research was the part time job student academic year 2014/2015 at English Department of Christian university of Indonesia Toraja. The result of the research showed that the learning strategies performed by this student were direct and indirect strategy. Direct strategy included memory, cognitive, compensation strategies while indirect strategy covered affective and social strategy.